APOCALYPSE NOW AND HEART OF DARKNESS: THE CLASH BETWEEN THE INDIVIDUAL AND THE SOCIETY - Silva, Lucas Calil Guimarães; Mancini, Renata Ciampone (Laboratório Editorial FCL-UNESP, 2014)
Francis Ford Coppola’s Apocalypse Now (1979), a film based on the romance Heart of Darkness, by Joseph Conrad, tackles the conflict between individual versus society in the Vietnam War context, between the 60s and 70s of the 20th century. This work aims to convey, following a semiotics approach, the director’s strategies to make this opposition explicit in the language of cinema at the same time that preserves the thematic fidelity in relation to the questions raised in the book about the British Imperialism of the 19th century in Africa.